2012
DOI: 10.1177/1550059411428718
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sleep Spindles and Clinical Recovery in Patients With Traumatic Brain Injury

Abstract: Few methods can predict the prognosis and outcome of traumatic brain injury. Electroencephalographic (EEG) examinations have prognostic significance in the acute stage of posttraumatic coma, and some EEG variables have been correlated with outcome. Furthermore, spindle activity and reactivity in the acute stage have been associated with good recovery. Assessments of consciousness based on EEG and magnetoencephalographic (MEG) recordings provide valuable information for evaluating residual function, forming dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 19 publications
3
26
0
2
Order By: Relevance
“…14 The presence of sleep-wake cycles defines the threshold between comatose states and consciousness. 15 Studies in patients undergoing rehabilitation following brain injury have suggested that the emergence of more complex sleep architecture parallels cognitive recovery [16][17][18][19] and correlates with improvement in clinical outcome in brain-injured adults 20 and children. 21 Furthermore, the presence of sleep spindles and rapid eye movement sleep in brain-injured patients in persistent vegetative or minimally conscious states predicted return to consciousness within 6 months.…”
mentioning
confidence: 98%
“…14 The presence of sleep-wake cycles defines the threshold between comatose states and consciousness. 15 Studies in patients undergoing rehabilitation following brain injury have suggested that the emergence of more complex sleep architecture parallels cognitive recovery [16][17][18][19] and correlates with improvement in clinical outcome in brain-injured adults 20 and children. 21 Furthermore, the presence of sleep spindles and rapid eye movement sleep in brain-injured patients in persistent vegetative or minimally conscious states predicted return to consciousness within 6 months.…”
mentioning
confidence: 98%
“…Medial components of the posterior intralaminar region of the central thalamus are involved in spindle generation. Therefore, the recovery of consciousness may be strongly associated with the recovery of sleep spindles after brain injury [30,31]. In patients who have TBI, findings of sleep architecture are inconsistent and may include; no changes, increased slow waves, decreased rapid eye movement sleep, increased rapid eye movement sleep during the second half of the night, no change in rapid eye movement sleep, or decreased onset latency of rapid eye movement sleep.…”
Section: Discussionmentioning
confidence: 99%
“…MEG remains an underused technology in TBI research 258,[326][327][328][329][330][331] and is not used routinely in clinical practice. The available data does not support the use of MEG in the diagnosis of TBI, as the quality of the evidence published to date is low with regard to this specific clinical application.…”
Section: Magnetoencephalographymentioning
confidence: 99%